Desenvolvimento de um posicionador automatizado com aplicação em medidas acústicas - Douglas Iceri Lasmar (2012)
The manual data collection is a process with limited repeatability and, often full time, depends on a performer of the experiment available. The need for automation of a manual data collection system increases, as the number of data to be acquired become larger or, when the executer of the experiment reaches its threshold, not being available to collect all the necessary data. This work will present the development of an automated data acquisition system for performing acoustic measurements in a bi-dimensional mesh to research the acoustic characteristics of a given material or area. For project execution, the work was divided into three main separate parts. The first part was the assemble of a mechanical displacement system (where the measurement sound sensors was attached) using trapezoidal screws, step motors and rectilinear guides. In the second part of the project, the electronics interface for the motion control and data collection was developed, comprising converters, amplifiers and the communication interface with the supervisory system. In the third and last part, was developed the control software for the survey device and for the signal processing interface. The Matlab software used to do the necessary mathematical implementation and to develop a graphical interface where the options are presented for collecting data. During the three steps all the assembly processes are detailed, the positioning module is metrological tested, presenting the correction equations for positioning, and the final prototype is experimentally tested. Finally all the results of the automatic data collection capacity are presented and compared.